A study on the correlation of clinical and ultrasound diagnosis of fetal growth restriction - Parul Shukla; Archana Singh; Sushma Ahirwal; Kirti Patel (Barpeta Obstetrics and Gynaecological Society, 2023)
Background: Fetal growth restriction (FGR), a condition occurring due to various reasons, is an important cause of fetal and neonatal morbidity and mortality. It has been defined as a rate of fetal growth less than normal in light of the growth potential of that specific infant. These infants have many acute neonatal problems that include perinatal asphyxia, hypothermia, hypoglycemia, and polycythemia. The likely long-term complications are growth retardation and major and subtle neurodevelopmental handicaps. Adequate surveillance of fetal growth is a crucial factor. Objective: To correlate clinical and ultrasound diagnosis of fetal growth restriction .Methodology: This prospective study was conducted in the Department of Obstetrics and Gynaecology at NSCB medical college, Jabalpur during the period of March 2018 to August 2019. Total 288 cases were included in the study. Results: The prevalence of FGR was found to be 33.7%. 60.81% of cases were in the age group 20-25 years. 89% of women belonged to rural areas. 67.30% of women belonged to the upper-lower class. The sensitivity and specificity of clinical methods were found to be 70.7% and 74.2% respectively. The sensitivity of ultrasonography and Doppler was 80.5% and 90.2%, and specificity was found to be 87.7% and 95.1% respectively. Out of 126 clinically suspected IUGR cases, overall 82 cases (65.1%) were confirmed as IUGR at birth. 43(20.63%) were lost to follow-up. Conclusion: The Doppler study is the best available modality for diagnosing FGR due to its high specificity, however clinical assessment, being a cost-effective screening tool, is equally good in diagnosing FGR.